PENGARUH SUBSTITUSI TEPUNG PORANG (Amorphophallus muelleri) PADA OTAK OTAK TANJUNG PINANG TERHADAP SIFAT FISIK DAN MUTU SENSORIS - Nuha, Havifah; Mahdiyah; Sachriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of porang flour substitution (Amorphophallus muelleri Bl.) in the manufacture of Tanjungpinang typical brains on physical properties and sensory quality. This research was conducted at the Food Processing Laboratory of the Culinary Education Study Program, State University of Jakarta from October 2025 to May 2026 using an experimental method. The research sample is typical Tanjungpinang otak-otak with porang flour substitution of 20%, 40%, and 60%. The initial testing involved five expert panelists who determined that the viable formulations of porang flour substitution to proceed were 20%, 40%, and 60%. Further testing involved 45 moderately trained panelists. Physical properties data in the form of folding and baked loss tests were analyzed using the ANOVA test followed by the Duncan test at a significance level of 5%. Sensory quality data were analyzed using the Kruskal–Wallis test. The results of the ANOVA test showed that the substitution of porang flour had a significant effect on the folding test value and baked loss. The results of the Duncan test showed that the highest folding test value was obtained in the substitution of 20% porang flour of 4.44 with very few crack categories. In the baked loss parameter, the lowest value was obtained in the substitution of 60% porang flour of 9.33%. The results of the Kruskal–Wallis test showed that the substitution of porang flour did not have a significant effect on sensory quality in terms of color, aroma, taste, and texture so that the entire formulation could still be accepted by the panelists. Based on the overall results of the study, the 40% porang flour substitution formulation is recommended as the best formulation because it produces optimal physical characteristics and sensory quality and has the potential to be further developed.